The adventures of Milo and Otis - Moore, Dudley; Hata, Masanori; Columbia TriStar Home Video (Firm); Columbia Pictures; Fujisankei Communication Production (Burbank, CA : Columbia TriStar Home Video, 1989)
Tells the story of the adventures of Milo the curious kitten and his friend Otis the pug-nosed puppy.
Originally released as a motion picture in 1989.
Based on an original story by Masanori Hata.
Cinematography, Hideo Fujii, Shinjo Tomita; art director, Takeharu Sakaguchi; special effects, Yoshio Kojima; editor, Chizucho Csada; music, Michael Boddicker.
Narrator: Dudley Moore.
MPAA rating: G.
VHS, Hi-fi stereo., Dolby surround.
Keywords: Hata, Masanori -- Film and video adaptations; Animals -- Juvenile drama; Film adaptations; Video recordings for the hearing impaired; Animals -- Drama; Closed captioning; Feature films